2021
DOI: 10.3389/fpsyg.2021.546896
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Growth in Postlingually Deaf Patients With Cochlear Implants: The Effect of Stress-Coping Strategies, Sociodemographics, and Deafness-Related Factors

Abstract: The aim of this study was to assess whether cochlear implant (CI) users who had been postlingually deaf developed a more positive outlook on life—the so-called posttraumatic growth (PTG)—as a result of their disability and to examine how PTG related to their stress-coping strategies and personal circumstances. The study group consisted of 119 postlingually deaf CI users. The participants were asked to anonymously fill in several questionnaires: the Post-Traumatic Growth Inventory (PTGI), Coping Orientations to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…As for the first part of the revealed gender differences, our results are fully consistent with the data of other researchers, most of whom have also reported significantly higher levels of posttraumatic growth in women than in men (e.g. Cohen-Louck, 2022;Fausor et al, 2022;Khechuashvili, 2018;Kobosko et al, 2021;Sicilia et al, 2022). Only some scientists have noted a lack of gendered differences in posttraumatic growth (Cundiff et al, 2023;Mesidor & Whaley, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…As for the first part of the revealed gender differences, our results are fully consistent with the data of other researchers, most of whom have also reported significantly higher levels of posttraumatic growth in women than in men (e.g. Cohen-Louck, 2022;Fausor et al, 2022;Khechuashvili, 2018;Kobosko et al, 2021;Sicilia et al, 2022). Only some scientists have noted a lack of gendered differences in posttraumatic growth (Cundiff et al, 2023;Mesidor & Whaley, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Quantitative studies have also shown that burn survivors experience posttraumatic growth after sustaining a burn injury (Hokes & Adams, 2022; Park & Lee, 2022). Posttraumatic growth, as a positive psychological experience for burn survivors, not only has positive impact on individuals' mental health, but can also reduce the stress caused by burn injury, motivate individuals to face the traumatic event with more positive coping styles (Kobosko et al, 2021), and ultimately promote physical and psychological recovery. Therefore, it is of great importance for healthcare professionals to identify the predictors of posttraumatic growth and take effective measures to promote posttraumatic growth among burn survivors.…”
Section: Introductionmentioning
confidence: 99%